Changes in active commuting and changes in health: Within- and between-individual analyses among 16 881 Finnish public sector employees - Haukka Eija; Gluschkoff Kia; Kalliolahti Essi; Lanki Timo; Jussila Juuso J; Halonen Jaana I; Oksanen Tuula; Salo Paula; Ervasti Jenni (Elsevier BV, 2025)
BACKGROUND
Active commuting, such as walking or cycling to work, can be beneficial for health. However, because within-individual studies on the association between change in active commuting and change in health are scarce, the previous results may have been biased due to unmeasured confounding. Additionally, prior studies have often lacked information about commuting distance.
METHODS
We used two waves (2020, T1 and 2022, T2) of self-report data from the Finnish Public Sector study (N = 16,881; 80% female) to examine the within- and between associations (in a hybrid model) between active commuting and health. Exposure was measured by actively commuted kilometers per week, that is, by multiplying the number of walking or cycling days per week with the daily commuting distance. The primary outcome, self-rated health, was measured at T1 and T2. The secondary outcomes, psychological distress, and sleep problems were measured only at T2 and were therefore analyzed only in a between-individual design.
RESULTS
After adjustment for potential time-varying confounders such as socioeconomic factors, body mass index, and health behaviors, an increase equivalent to 10 additional active commuting kilometers per week was associated with a small improvement in self-rated health (within-individual unstandardized beta = 0.01, 95% CI 0.01-0.02; between-individual unstandardized beta = 0.03, 95% CI 0.02-0.04). No associations were observed between changes in active commuting and psychological distress or sleep problems.
CONCLUSIONS
An increase in active commuting may promote self-rated health. However, increase of tens of additional kilometers in commuting every day may be required to produce even a small effect on health.